All you need to know about the music business - Passman, Donald S.; Glass, Randy (2015)
"For more than twenty years, All You Need to Know About the Music Business has been universally regarded as the definitive guide to the music industry. Now in its ninth edition, this latest edition leads novices and experts alike through the crucial, up-to-the-minute information on the industry's major changes in response to today's rapid technological advances and uncertain economy,"--Amazon.com.
pt. VIII. Motion picture music. Overview of motion picture music (Introduction; One song : eight deals; The rights involved) -- Performer deals (Overview; Performance in the film (no record rights); Record rights to film performance) -- Film songwriter deals (Terminology; Deal points) -- Composer agreements (Deal points; Package deals; Creative financing; Television composers; Video game composers) -- Licensing existing recordings and existing songs for motion pictures (Master licenses; Licensing existing musical compositions for films; Film music quiz) -- Music supervisors (Role; Fees and royalties; Television supervisors) -- Soundtrack album deals (Score albums; Song albums; Cost covering; Other issues).
Includes index.
Keywords: Music trade -- United States; Music -- Economic aspects -- United States; Copyright -- Music -- United States; Popular music -- Writing and publishing; Copyright -- Music; Music -- Economic aspects; Music trade; United States; Music industry; Music jobs